Thermoelectric transport properties of PbS and its contrasting electronic band structures. (August 2020) - Qin, Yongxin; Wang, Dongyang; Hou, Zhenghao; Xiao, Yu; Wang, Guangtao; Huang, Zhiwei; Zhao, Li-Dong
Abstract: In this work we investigated the thermoelectric transport behaviors of p -type PbS and n -type PbS with an emphasis on its contrasting electronic band structures. We found that the Seebeck coefficients of p -type PbS increased faster with rising temperature than that of n -type PbS with the same carrier concentration. The Density functional theory (DFT) calculation of the energy band structure of PbS as a function of temperature illustrates a significant contribution from multiple valence bands in K-doped p -type PbS. This work revealed one important information that manipulating electronic bands is also suitable in developing high-performance PbS thermoelectric systems. Graphical abstract: PbS possesses both multiple conduction bands and multiple valence bands. With rising temperature, valence bands illustrate a more pronounced converging trend than conduction bands, which results in higher Seebeck coefficients in p -type PbS at 523–823 K than that of n -type PbS with the same carrier concentration. Image, graphical abstract